Hanif'in Manzum Kırk Hadis Tercümesi Şerhi - Aksu, Cemal (Gökkubbe, 2004)
lt has become traditional in eastem civilizations to produce works containing 40 hadith since the second century of the Islamic calendar. The purposes of the authors in doing this, among many others, are gaining the Prophet's praise and affection, being benefıcial to people and presenting their work to statespersons. Turkish literature had yielded some outstanding examples in this tradition. The work of Hanif, an 18th century poem, "Poetic Explanation of 40 Hadith" is a work of this kind.
Hanif's Poetic Explanation of 40 Hadith
Keywords: Kırk Hadis; Hanif; Kırk Hadith of the Hanif